FRAGMENTASI POLITIK REPOSISI PARTAI DALAM PENCARIAN FORMAT IDEAL PASCA REFORMASI - AHMAD, ZAMZAMI (Fakultas Hukum, Universitas Islam Balitar, 2025)
The Indonesian party system post-reform is expected to become a pillar of substantive democracy; however, in practice, it faces various serious problems such as extreme multi-party fragmentation, elite oligarchic domination, ideological erosion, and weak internal democracy. As a result, political parties fail to perform their functions of representation, political education, and cadre development, leading to a legitimacy crisis and weakening government effectiveness. Although various studies have identified these issues, there remains a gap in formulating a new comprehensive party system format that not only addresses structural and ideological problems but is also compatible with Indonesia's presidential system. This research aims to examine the dynamics and challenges of political parties post-reform and to formulate an ideal party system format that aligns with the principles of substantive democracy. Through a qualitative-descriptive approach and literature study, the research findings indicate that institutional reform, ideological strengthening, funding transparency, and internal party democratization are the main prerequisites. Thus, the party system can be repositioned as the foundation of democracy, rather than merely an elite power struggle tool.